Students' Mathematical Connection Ability in Solving Circle Problems Based on Gender and Learning Motivation Perspectives - Siagian, Teddy Alfra; Agustinsa, Ringki; Zianti, Chepy Hyva (Jurnal Pendidikan MIPA, 2022)
This study aims to determine the relationship between gender and student learning motivation on students' mathematical connection abilities in solving problems on circle material. Mixed method research design applied in this study. The subjects of this study were 34 class VIII students of SMPN 1 Bengkulu City. The sampling technique was carried out by purposive random sampling. Data collection techniques used mathematical connection ability test questions, learning motivation questionnaires, and interviews. The chi-square test does hypothesis testing. The results showed: (1) there was no significant relationship between gender and students' mathematical connection abilities, (2) a significant relationship between learning motivation and students' mathematical connection abilities with a correlation index in the medium category. The results of this study also show that male students with high learning motivation have high mathematical connection abilities on all indicators. In contrast, female students with high learning motivation have higher mathematical connection abilities when connecting mathematical concepts. Keywords: mathematical connection ability, learning motivation, mixed method research. DOI: http://dx.doi.org/10.23960/jpmipa/v23i4.pp1683-1699